A survey of the reading interests of grades three to six pupils of UP Integrated School - Somera, Patricia V.; Hidalgo, Namnama P.; Picache, Ursula G. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1984)
The study was undertaken to identify the reading interests of grade three to six pupils of the UP Integrated School (UPIS) and determine if any significant differences in reading interests exist among different grade levels, sexes, and ability groupings.
Data was gathered through the questionnaire which consists of thirteen questions divided into two sections: personal traits and media habits. The school librarian and the teacher-in-charge were interviewed. Four hundred and seventy-seven third to sixth grades constituted the population of this study. Responses were tabulated and rank order of items were determined to facilitate the analysis of data.
The chi-square test was used to find out if significant differences exist in the reading interests of pupils in different grade levels, sex, and ability.
Grade level, sex, and ability do affect the reading interests of the third to sixth graders of the UP Integrated School. Though the third to sixth grades were found to be avid readers, the grade four pupils read most often followed by grades five and three.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: Books and reading for children -- Philippines -- Quezon City; Reading interests -- Philippines -- Quezon City; University of the Philippines Integrated School